Flora arbórea de la universidad de Córdoba, Colombia (2017)
The article addresses the topic of arborisation on university campuses and its principal aim is determine the structure and composition of the tree planting in the headquarters of the University of Córdoba, in the city of Monteria, Colombia. It outlines the problems generated by urban tree planting in the American Tropic since most of them rely on the use of introduced species, in detriment of native flora and fauna. As a methodology, fieldwork was carried out in ten strategic points of the campus, where photographic samples were taken and then collated with a series of scientific documents for its identification. The results highlight the identification of 143 species grouped in 119 genera and 39 families. It is concluded that it is urgent to create a management plan to conserve and improve the trees of the campus.